2023
DOI: 10.3847/2041-8213/acac9e
|View full text |Cite
|
Sign up to set email alerts
|

PHANGS–JWST First Results: Rapid Evolution of Star Formation in the Central Molecular Gas Ring of NGC 1365

Abstract: Large-scale bars can fuel galaxy centers with molecular gas, often leading to the development of dense ringlike structures where intense star formation occurs, forming a very different environment compared to galactic disks. We pair ∼0.″3 (30 pc) resolution new JWST/MIRI imaging with archival ALMA CO(2–1) mapping of the central ∼5 kpc of the nearby barred spiral galaxy NGC 1365 to investigate the physical mechanisms responsible for this extreme star formation. The molecular gas morphology is resolved into two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 120 publications
2
18
0
Order By: Relevance
“…This region hosts an AGN, forms stars at a rate of order ∼10 M e yr −1 , and represents a distinct regime from our other targets in terms of gas surface density, star formation intensity, and dust properties. We focus this paper on normal galaxy disks and leave the contrast between disk and starburst environments for future work, but note that several other papers in this Issue focus specifically on this rich region in NGC 1365 (Liu et al 2023;Schinnerer et al2023;Whitmore et al2023). For the correlations, we do plot the data from this higher intensity region but indicate the region excluded from statistical analysis by shading.…”
Section: Data Selectionmentioning
confidence: 99%
“…This region hosts an AGN, forms stars at a rate of order ∼10 M e yr −1 , and represents a distinct regime from our other targets in terms of gas surface density, star formation intensity, and dust properties. We focus this paper on normal galaxy disks and leave the contrast between disk and starburst environments for future work, but note that several other papers in this Issue focus specifically on this rich region in NGC 1365 (Liu et al 2023;Schinnerer et al2023;Whitmore et al2023). For the correlations, we do plot the data from this higher intensity region but indicate the region excluded from statistical analysis by shading.…”
Section: Data Selectionmentioning
confidence: 99%
“…This ends up covering a region of ∼15″ in diameter (∼1.3 kpc in these targets). Some other bright sources in the center of NGC 1365 are also saturated and not included in this analysis, though these are further explored in Schinnerer et al (2023) and Liu et al (2023).…”
Section: Compact Source Identification and Photometrymentioning
confidence: 99%
“…Based on our CIGALE fits, we see only a few high-mass clusters (>10 4 M e ) in NGC 1365 that are deeply embedded (below the black dashed line). These objects are explored more in Whitmore et al (2023), Schinnerer et al (2023), andLiu et al (2023). For low mid-IR luminosities, all of the young (<10 Myr) embedded sources have SED fits that also find lowmass measurements (M < 10 3 M e ), reaching levels where stochastic sampling of the IMF can become important (da Silva et al 2012) and a cluster may not form stars with significant ionizing flux.…”
Section: A Dearth Of Embedded Sourcesmentioning
confidence: 99%
“…Hoyer et al (2023) studied the nuclear star cluster in NGC 628 and the nature of the mid-infrared structure surrounding it. Schinnerer et al (2023) showed that massive, dusty clusters can provide a sensitive diagnostic of the very dusty star-forming environments in nuclear regions when comparing ALMA data and simulations. Some of the clusters detected in the PHANGS-JWST survey push current stellar and dust models used by CIGALE to their limits due to their very young ages, high dust content, and/or low mass.…”
Section: Constraining the Natal Cluster Mass Function And Clustermentioning
confidence: 99%
“…The PHANGS-JWST first results on stellar clusters illustrate the potential (and challenges) in using the data at their highest resolution (which at 2 μm surpasses the resolution of HST optical imaging) to develop catalogs of embedded star clusters, augment the PHANGS-HST star cluster and association catalogs 81 with photometry from 2 to 21 μm, and measure their physical properties through SED fitting (Whitmore et al 2023b;Hoyer et al 2023;Rodriguez et al 2023). Catalogs of compact sources in the MIRI bands can be produced to identify larger star-forming regions on scales comparable to the H II regions observed with MUSE and the giant molecular clouds resolved by ALMA (Hassani et al 2023;Schinnerer et al 2023). As PHANGS-JWST analysis matures, it will be possible to develop complete catalogs of dust-enshrouded and visible stellar populations across multiple physics scales (Larson et al 2022), which include physical properties such as mass, age, and dust reddening, via SED fitting, which is able 79 CANFAR PHANGS-JWST Treasury Survey Data publication: doi:10.11570/22.0082.…”
Section: Data Productsmentioning
confidence: 99%